![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\left\{{}\begin{matrix}\left(x-2\right)^2\ge0\\\left(y+3\right)^2\ge0\end{matrix}\right.\Rightarrow\left(y-2\right)^2+\left(y+3\right)^2\ge0\)
Mà \(\left(x-2\right)^2+\left(y+3\right)^2=0\)
\(\Rightarrow\left\{{}\begin{matrix}\left(x-2\right)^2=0\\\left(y+3\right)^2=0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x-2=0\\y+3=0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x=2\\y=-3\end{matrix}\right.\)
Vậy \(x=2;y=-3\)
b) \(\left\{{}\begin{matrix}\left(x+1\right)^2\ge0\\2\left|y-1\right|\ge0\end{matrix}\right.\Rightarrow\left(x+1\right)^2+2\left|y-1\right|\ge0\)
Mà \(\left(x+1\right)^2+2\left|y-1\right|=0\)
\(\Rightarrow\left\{{}\begin{matrix}\left(x+1\right)^2=0\\2\left|y-1\right|=0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x+1=0\\y-1=0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x=-1\\y=1\end{matrix}\right.\)
Vậy x = -1; y = 1
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có: \(\widehat{xAy}=\widehat{x'Ay'}\) (đối đỉnh)
\(\Rightarrow\widehat{xAy}=\widehat{x'Ay'}=\frac{\widehat{xAy}+\widehat{x'Ay'}}{2}=\frac{140^0}{2}=70^0\)
Có: \(\widehat{xAy}+\widehat{x'Ay}=180^0\left(kề-bù\right)\)
\(\Rightarrow\widehat{x'Ay}=180^0-\widehat{xAy}=180^0-70^0=110^0\)